ANALISIS BIAYA OPERASIONAL KENDARAAN BERDASARKAN KECEPATAN RATA-RATA PERJALANAN DI JALAN MAJAPAHIT KOTA MATARAM - HASYIM HASYIM; ROHANI ROHANI (Universitas Mahasaraswati K. Mataram, 2024)
The city of Mataram, the center of trade, offices, and education, experienced an increase in population and vehicles. The 2023 data recorded 441.147 thousand residents and 385,579 motor vehicles. The increase in traffic volume on road Majapahit has an impact on traffic performance and vehicle operating costs. The study entitled